Seabed classification around Lampione islet, Pelagie Islands Marine Protected area, Sicily Channel, Mediterranean Sea. Issue 2 (3rd July 2019) - Innangi, Sara; Di Martino, Gabriella; Romagnoli, Claudia; Tonielli, Renato
ABSTRACT: We present the first seabed map of the shallow-water areas of Lampione, the islet of the Pelagie Islands Marine Protected Area (Sicily Channel, Italy). The seafloor was mapped from the coast to a depth of about 75 m, using high-resolution multibeam systems (both for bathymetry and backscatter) along with ground-truth data in the form of grab samples and ROV video-observations. By integrating these original data, a first seabed classification was produced through the use of the Remote Sensing Object Based Image Analysis, a semi-automatic segmentation approach. The resulting 1: 5.000 scale map includes sediment types and habitat distribution contributing to the knowledge of the peculiar marine ecosystem observed at Lampione. In particular, the map provides the first indication of the wide occurrence of rhodolith/maërl habitats at Lampione, which are among the most important ecosystems in the Mediterranean Sea.